WATER CONSERVATION AND BUSINESS RESEARCH: THEMES AND GLOBAL COLLABORATION, 1916–2025 - Prabowo, Riefky (Journal of Innovation Research and Knowledge, 2025)
This study utilizes bibliometrics to examine global water conservation and business studies from 1916 to 2025. We investigated 3,083 Scopus publications on water conservation and business. The Bibliometric package in R, Biblioshiny for visualization. Annual publishing growth, significant nations, co-authorship networks, theme changes, and keyword trajectories are examined. The US leads in citations and international collaboration with 22.12% of documents, indicating a consistent increase in scientific production since the early 2000s. Thematic mapping shows established themes like environmental protection and sustainable development alongside underdeveloped but crucial ones like water supply and management. This field is globally as shown by important research in agroecology, hydrology, and environmental economics. Keyword analysis shows that business-related water research is using terms connected to sustainability. Research on scholarly trends and global collaborations over a century informs sustainable business practices and policymakers with evidence-based ideas.